(untitled) (Research, Society and Development, 2021)
To investigate the general prevalence of sexually transmitted infections (STIs) and the factors associated with syphilis and HIV in women treated in the Integrated Health System (SINAS). Cross-sectional database study with 6.993 patients treated at a referral center in the state of Paraná, Brazil, from January 2013 to December 2015. The overall prevalence was 2.39% for syphilis and HIV, being 0.65 and 0.22% for pregnant women and 3.07 and 0.78% for non-pregnant women, respectively. After adjusting the variables in the logistic regression model, the main predictors associated with syphilis were the age groups 41 to 59 and 60 to 83 years old (p <0.001), non-pregnant women (p <0.01), marital status married (p <0.001), drug use (p <0.01) and previous STIs (<0.001). For HIV, the predictors were city of residence (<0.001), reason for search (p <0.01), reported previous STTs (p <0.001). The population served had a higher prevalence of syphilis when compared to the international panorama, while the HIV values were lower. The predictors associated with STIs were non-pregnant, heterosexual women, aged between the second and fourth decade of life, higher education and who did not use condoms regularly. This study presents relevant information for the evaluation and development of measures that prevent, control and are related to the diagnosis and treatment of the investigated STIs.